1989
DOI: 10.1073/pnas.86.7.2204
|View full text |Cite
|
Sign up to set email alerts
|

On the origin and transmission of force in actomyosin subfragment 1.

Abstract: A proximity map showing the three-dimensional arrangement of 12 chemically defined points in actomyosin subfragment 1 is developed and roughly correlated with published electron microscope reconstructions of others. Several additional points and topological relationships in the primary polypeptide chain folding are assimilated into this model. Certain crossliikings and distance change observations are interpreted as indicators of transmission of force/displacement between the nucleotide-binding and an actin-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 61 publications
3
51
0
Order By: Relevance
“…It is expected that any other residue in this latter location would alter the conformation of this segment and change the domain-domain interactions. Chemical and structural studies of myosin have indicated that there must be a significant structural rearrangement associated with the reactive sulffihydryl groups during the contractile cycle (38)(39)(40)(41). In the structure of chicken skeletal myosin Si, these two residues are separated by an a-helix where their side chains point in opposite directions (23), yet they can be cross-linked in the presence of nucleotide (42)(43)(44) and chemical modification of the cysteines changes the kinetic properties of myosin (45,46).…”
Section: Resultsmentioning
confidence: 99%
“…It is expected that any other residue in this latter location would alter the conformation of this segment and change the domain-domain interactions. Chemical and structural studies of myosin have indicated that there must be a significant structural rearrangement associated with the reactive sulffihydryl groups during the contractile cycle (38)(39)(40)(41). In the structure of chicken skeletal myosin Si, these two residues are separated by an a-helix where their side chains point in opposite directions (23), yet they can be cross-linked in the presence of nucleotide (42)(43)(44) and chemical modification of the cysteines changes the kinetic properties of myosin (45,46).…”
Section: Resultsmentioning
confidence: 99%
“…The proposed assignment of sequence B in myosin patterns represented by EX2RX,GX,(IL)X(FY)X(DE), may have interesting implications regarding the folding Table 2 Results The proximity of elements of the two consensus sequences is also predicted by the recent 3D-lattice model of Botts et al [13], which is based primarily on fluorescence energy transfer measurements. Such an arrangement of the two sequences would imply that regions of both the 27-kDa and 21-kDa segments may contribute to the ATPase site in myosin Sl, and that these two segments, which are well separated in the primary sequence, may not be separate domains as has been suggested from limited proteolysis studies [ 14,151. Recent studies on the progressive unfolding of Sl indicate that the Sl structure may be comprised of a stable domain consisting of the interacting 21-kDa, 27-kDa, and light chain, and a less stable middle 50-kDa segment [ 16,171.…”
Section: Resultsmentioning
confidence: 76%
“…These sites had previously been shown to be remote from each other [94,95]. Because the kinetic data indicate that the binding affinity of S1 distinct ATP and actin-binding sites and in transmitting changes to the lever arm [35].…”
Section: Why Study Opening and Closing Of 50 Kda Cleftmentioning
confidence: 96%